Captivity Influences Gut Microbiota in Crocodile Lizards (Shinisaurus crocodilurus) - Tang, Guo-Shuai; Liang, Xi-Xi; Yang, Meng-Yuan; Wang, Ting-Ting; Chen, Jin-Ping; Du, Wei-Guo; Li, Huan; Sun, Bao-Jun (Frontiers in Microbiology, 2020)
Captivity is an important measure for conservation of an endangered species and it is becoming a hot topic in conservation biology, which integrates gut microbiota and endangered species management in captivity. As an ancient reptile, the crocodile lizard (Shinisaurus crocodilurus) is facing extreme danger of extinction, resulting in great significance to species conservation in the reserve. Thus, it is critical to understand the differences in gut microbiota composition between captive and wild populations, as it could provide fundamental information for conservative management of crocodile lizards. Here, faecal samples of crocodile lizards were collected from two wild and one captive populations with different ages (i.e. juveniles and adults), and were analyzed for microbiota composition by 16S rRNA gene amplicon sequencing. This study showed that the lizard gut microbiota was mainly composed of Firmicutes and Proteobacteria. The gut microbiota composition of crocodile lizard did not differ between juveniles and adults, as well as between two wild populations. Interestingly, captivity increased community richness and influenced community structures of gut microbiota in crocodile lizards, compared with wild congeners. This was indicated by higher abundances of the genera Epulopiscium and Glutamicibacter. These increases might be induced by complex integration of simple food resources or human contact in captivity. The gut microbiota functions of crocodile lizards are primarily enriched in metabolism, environmental information processing, genetic information processing, and cellular processes based on the KEGG database. This study provides fundamental information about the gut microbiota of crocodile lizards in wild and captive populations. In the future, exploring the relationship among diet, gut microbiota, and host health is necessary for providing animal conservation strategies.